The importance of having a paid job. Gendered experiences of health and ill-health in daily life among middle-aged women and men - Anne Hammarström (BMC, 2021)
Abstract Background More gender-theoretical studies are needed to gain a deeper understanding of what life circumstances make people sick or improve their health. The aim of the study was to gain a deeper understanding of social determinants of health by exploring gendered experiences in daily life among middle-aged women and men using the theory of gender relations. Methods Individual interviews with nine men and women were performed, focusing on what made them feel good or bad. Qualitative content analysis was used to analyse the data. Results A major theme in our interviews was the gendered health-promoting experiences related to having a job, which involved becoming someone, feeling appreciated at work and having control over work. Having good family relations was also health-promoting, in terms of supportive relations and becoming a parent. Ill-health was related to gendered adverse conditions at work (accidents, monotonous and stressful work tasks, being bullied) and in domestic life (demands, destructive partner relations, having children with problems). Conclusions Gendered determinants of health and ill-health were identified in both working and domestic life. Public health policy needs to challenge the gender order in society, which defines the gendered structure of the labour market as well as the gendered relations in domestic life.